RAQAMLASHTIRISH SHAROITIDA BO‘LAJAK O‘QITUVCHILAR KREATIV KOMPETENTLIGINI RIVOJLANTIRISH MAZMUNI - Rasulova, Z.D. (SCIENCE and SOCIETY, 2024)
In the article, the need to use digital technologies is theoretically based educational processes of higher education institutions. Ways to create opportunities for effective use of e-learning for future specialists by organizing a digital audience, and to develop independent and creative approach skills.
Keywords: creativity; creative competence; thinking; digital technologies; digital transformation; e-learning; forms of digitalization of the educational environment; qualities of a creative personality; digital auditory; integration